2017
DOI: 10.1016/j.crpv.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Morphological correlates of the first metacarpal proximal articular surface with manipulative capabilities in apes, humans and South African early hominins

Abstract: This study quantifies the metacarpal 1 (MC 1) proximal articular surface using three-dimensional morphometrics in extant hominids and fossil hominins (SK 84, cf + Paranthropus robustus/Homo erectus and StW 418, . Australopithecus africanus) to understand which characteristics of the proximal metacarpal 1 are potentially correlated with human manipulative abilities and if they can be used in a paleoanthropological setting. A principal components (PC) analysis was used to compare MC 1 proximal articular surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 58 publications
4
42
0
Order By: Relevance
“…While values average DA values for this species were highest in the radiopalmar region (Figure b) consistent with opposition of the thumb these were only significantly higher than those of bonobos (Figure ) and DA were also higher at some ulnar landmarks (Figure b). Conversely, humans displayed the highest RBV/TV values at the radial and less extreme palmar region of Mc1 base landmarks, consistent with a habitually and forcefully abducted thumb, flexed in opposition ( H2c ; Napier, ; Halilaj, Rainbow, et al, ; Feix et al, ; D'Agostino, Dourthe, Kerkhof, Stockmans, et al, , Marchi et al, ). These results agree with other studies that have found a palmar concentration of Mc1 base BV/TV in comparison to other apes (Skinner et al, , ) and other metacarpals (Wong et al, ).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…While values average DA values for this species were highest in the radiopalmar region (Figure b) consistent with opposition of the thumb these were only significantly higher than those of bonobos (Figure ) and DA were also higher at some ulnar landmarks (Figure b). Conversely, humans displayed the highest RBV/TV values at the radial and less extreme palmar region of Mc1 base landmarks, consistent with a habitually and forcefully abducted thumb, flexed in opposition ( H2c ; Napier, ; Halilaj, Rainbow, et al, ; Feix et al, ; D'Agostino, Dourthe, Kerkhof, Stockmans, et al, , Marchi et al, ). These results agree with other studies that have found a palmar concentration of Mc1 base BV/TV in comparison to other apes (Skinner et al, , ) and other metacarpals (Wong et al, ).…”
Section: Discussionmentioning
confidence: 62%
“…Many landmark sets have been used to analyze the primate Mc1 proximal base (Marchi et al, ; Niewoehner, ), and recently a set has been used to analyze the shape of the primate Mc1 head (Galletta, Stephens, Bardo, Kivell, & Marchi, ). The location and type (Bookstein, ) of anatomical landmarks used here for the head and base of Mc1 are given in Tables and , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many landmarks have been identified on the non‐pollical metacarpals for morphometric studies (Susman, ; Inouye, ; Drapeau, ), but there have been relatively few studies that have applied GM methods to the primate metacarpus, and these have focused on the Mc1 base (Niewoehner, ; Marchi et al. ). Metatarsals are developmental serial homologues of metacarpals (Rolian et al.…”
Section: Methodsmentioning
confidence: 99%
“…High mobility at the TMCJ plays a key role in the pad-to-pad opposition abilities of the 358 human hand, in which the thumb is able to rotate and touch the apical tip of each 359 phalanx. In many human manipulative activities like precision grips the thumb needs 360 to be highly abducted, which means that the load is radially shifted on the joint surface 361 (Lewis, 1977;Marchi et al, 2017). The observed larger radially extended proximal 362 surface is therefore important because, whilst it allows for a greater radial extension, 363 it also helps the joint resist high levels of radial displacement by providing a greater 364 surface area for the abducted MC1 (Hamrick, 1996).…”
mentioning
confidence: 99%